Does anonymising job applications reduce gender bias?: Understanding managers' perspectives. Issue 8 (6th November 2018) - Foley, Meraiah; Williamson, Sue
Abstract : Purpose: Anonymous recruitment seeks to limit managers' reliance on stereotypes in employment decisions, thereby reducing discrimination. This paper aims to explore how managers interpret the information embedded in anonymised job applications and how they interpret the organisational priorities driving the adoption of anonymous recruitment. Design/methodology/approach: Semi-structured interviews with 30 managers in two Australian public sector organisations were analysed. Findings: The results showed that managers used implicit signals and cues to infer the gender identities of applicants in anonymised applications, reintroducing the possibility of bias. Managers perceived that anonymous recruitment sent positive external signals to prospective employees but were sceptical about its effectiveness. Research limitations/implications: The results showed that removing applicants' names and identifying information from applications may not be sufficient to reduce bias. In organisations where managers are sympathetic to equity and diversity issues, use of anonymous recruitment may provoke resentment if managers perceive organisational distrust or inconsistent objectives. Limitations regarding the size and nature of the sample are acknowledged. Practical implications: Organisations seeking to reduce gender discrimination in recruitment may consider adopting standardised application procedures or training managers to understand how stereotypes affect evaluations. Organisations should also assess managerial support for, and understanding of, anonymous recruitment prior to implementation. Originality/value: The findings add to existing knowledge regarding the effects of implicit gender signals in managers' assessments and the effectiveness of anonymous recruitment in reducing gender bias. It also contributes to signalling theory by examining how managers interpret the signals conveyed in organisational policies.